Hubungan keragaman konsumsi pangan dan asupan zat gizi dengan kejadian stunting pada balita usia 24-59 bulan - Karlina Karlina; Lilik Hidayanti; Taufiq Firdaus Al Ghifari Atmadja (Nutrition Scientific Journal, 2023)
Stunting as a result of chronic nutritional problems in the long term. Height for age -2 Standard Deviation (SD) is called stunting. This study aims to analyze the relationship between the diversity of food consumption and nutrient intake with the incidence of stunting in toddlers aged 24-59 months. The method of this research was analytic observational with cross sectional design. The population of this study were all children under five in Sukaratu Village, Sukaresik District as many as 364 people. The subject of this study was toddlers aged 24-59 months, obtained as many as 76 subject. Sampling using Proportional Random Sampling technique. The statistical test used is Chi-square. There was a significant relationship between stunting and food diversity (OR 6,1) energy intake (OR 5,6), protein intake (OR 8,8), carbohydrate intake (OR 3.9), and fat intake (OR 8,5). Keywords: diversity of food consumption, nutrient intake, stunting, toddler